Diet-induced ketosis in adult patients with subacute acquired brain injury: a feasibility study - Edwards, Maria G. P.; Andersen, Jens R.; Curtis, Derek J.; Riberholt, Christian G.; Poulsen, Ingrid (Frontiers in Medicine, 2024)
Background Research in animal models on cerebral metabolism after brain injury highlights the potential benefits of ketosis in reducing secondary brain injury, but studies in humans are lacking. Aim This study aimed to examine if a 6-week ketogenic diet intervention with added medium-chain triglycerides (MCT) was feasible in adult patients with acquired brain injury in the subacute phase, whether ketosis could be achieved and maintained, and to what extent serious adverse reactions, adverse reactions, serious adverse events, and adverse events occured. Methods Patients ≥18 years of age diagnosed with subacute acquired brain injury and an expectation of hospitalisation ≥6 weeks were included in the intervention group. Patients not included in the intervention group were included in a standard care reference group. The intervention consisted of a ketogenic diet supplemented with MCT to obtain a plasma concentration of β-hydroxybutyrate (BHB) ≥0.5 mmol/L. Patients who were enterally fed were given KetoCal® 2.5:1 LQ MCT Multi Fiber (Nutricia A/S, Allerød, Denmark), supplemented with Liquigen® (Nutricia A/S, Allerød, Denmark). Patients consuming oral nutrition were given KetoCal® 2.5:1 LQ MCT Multi Fiber supplemented with Liquigen®, in addition to ketogenic meals. Results During a 13-week inclusion period, 12 of 13 eligible patients (92% [95% CI: 67% to 99%]) were included in the intervention group, and 17 of 18 excluded patients (94% [95% CI: 74% to 99%]) were included in the reference group. Eight patients (67%) completed the 6-week intervention. It took a median of 1 day to achieve ketosis from starting a 100% MCT ketogenic diet, and it was maintained for 97% of the intervention period after ketosis was obtained. There were no serious adverse reactions to the MCT ketogenic diet, and patients experienced adverse reactions not considered serious in 9.5% of days with the intervention. The MCT ketogenic diet was accepted by patients on all intervention days, and in the two patients transitioning from enteral feeding to oral intake, there were no complications related to transitioning. Conclusion Intervention with MCT ketogenic diet is feasible and tolerated for 6 weeks in hospitalised adult patients with subacute acquired brain injury. Randomised controlled trials are needed to assess the benefits and harms of the MCT ketogenic diet and the effect on patients’ recovery. Clinical trial registration:ClinicalTrials.gov, identifier [NCT04308577].